KEPUASAN MAHASISWA TERHADAP PELAYANAN ADMINISTRASI PRODI MANAJEMEN ADMINISTRASI AKADEMI MANAJEMEN BELITUNG - Tartini Tartini (Program Studi Akuntansi, 2022)
This study aims to determine student satisfaction with administrative management services based on Tangibles, Responsiveness, Reliability, Empathy, and Assurance aspects. This study is a descriptive study with a quantitative approach. The population and sample of this study were 34 administrative management students. The sampling technique was used proportional stratified random sampling. data collection using an attitude scale. The data analysis technique used a trend test and the percentage of the frequency distribution for each aspect of satisfaction. The results of this study indicate: 1) Student satisfaction based on Tangibles aspect in general has a value of 75%, 2) Student satisfaction based on Responsiveness aspect generally has a value of 71%, 3) Student satisfaction based on Realibility aspect generally has a value of 70%, 4) Student Satisfaction based on the Empathy aspect in general has a value of 72%, 5) Student Satisfaction based on the Assurance aspect in general has a value of 73%.